2012
DOI: 10.4041/kjod.2012.42.1.39
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of three different orthodontic wires for bonded lingual retainer fabrication

Abstract: ObjectiveWe evaluated the detachment force, amount of deformation, fracture mode, and pull-out force of 3 different wires used for bonded lingual retainer fabrication.MethodsWe tested 0.0215-inch five-stranded wire (PentaOne, Masel; group I), 0.016 × 0.022-inch dead-soft eight-braided wire (Bond-A-Braid, Reliance; group II), and 0.0195-inch dead-soft coaxial wire (Respond, Ormco; group III). To test detachment force, deformation, and fracture mode, we embedded 94 lower incisor teeth in acrylic blocks in pairs.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
46
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 17 publications
5
46
0
Order By: Relevance
“…Bearn et al 20 claimed that wires with a larger diameter and greater surface area require greater force to pull the wire out from the composite resin. However, Baysal et al 21 found that the Penta One wire exhibited the highest mean resistance to displacement from composite resin, even though it was not the wire with the largest diameter.…”
Section: Discussionmentioning
confidence: 98%
“…Bearn et al 20 claimed that wires with a larger diameter and greater surface area require greater force to pull the wire out from the composite resin. However, Baysal et al 21 found that the Penta One wire exhibited the highest mean resistance to displacement from composite resin, even though it was not the wire with the largest diameter.…”
Section: Discussionmentioning
confidence: 98%
“…These studies also evaluated the amount of deflection brought about by the debonding force but not the magnitude of force needed for unit deformation. [ 7 8 9 ] Therefore, the present study was designed to evaluate and compare the bond strength of three commonly used fixed retainer wire-composite system including the three-stranded twisted retainer wire (3M Unitek) as well as the LDR for 0.5 mm deformation in these lingual retainer wires.…”
Section: Introductionmentioning
confidence: 99%
“…Bearn et al8 studied the effect of type of wire and type of composite and composite blocks. A few in vitro studies have compared the bonding strengths of lingual retainers with different combinations of wires and resins 9,10. Cooke and Sherriff9 performed an in vitro evaluation of the vertical force necessary for debonding lingual retainers constructed of different kinds of wires.…”
Section: Introductionmentioning
confidence: 99%